Acute Coronary Syndrome as an Unusual Initial Presentation of T-Prolymphocytic Leukemia: A Case Report and Review of the Literature - Christian R. Klein; Felix Jansen; Peter Brossart; Marco Herling; Georg Feldmann (Case Reports in Hematology)
T-prolymphocytic leukaemia (T-PLL) is the most common mature T-cell leukaemia in Central Europe and is often manifested by rapidly increasing lymphocytosis, marked bone marrow infiltration and splenomegaly. In 10–15% of cases, the diagnosis is made by incidental findings in otherwise asymptomatic patients. Here we report a case of T-PLL that initially became symptomatic due to the presence of acute coronary syndrome (ACS). Initially, emergency coronary angiography with consecutive emergency 5-coronary artery bypass grafting (CABG) was performed. Leukocytosis was found perioperatively and T-PLL (with TCL1 rearrangement) was subsequently diagnosed. Despite known potential cardiotoxicity, the patient was treated with the anti-CD52 antibody alemtuzumab with a gradual dose increase from 3 mg to 30 mg per day. Systemic alemtuzumab therapy resulted in the complete remission of T-PLL in the bone marrow without any impairment to cardiac function. The patient was then eligible to undergo a consolidating allogeneic stem cell transplant (alloSCT). The reported case shows that T-PLL can also become initially symptomatic through an acute coronary syndrome on the basis of complex coronary heart disease. Targeted antileukaemic therapy with the monoclonal antibody alemzutumab can lead to effective systemic cytoreduction without cardiac dysfunction even in patients with severe cardiac disease, although cases of cardiotoxicity have been reported.